2014
DOI: 10.1021/ja4126998
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate-Induced Structural Changes in 1–3 nm Platinum Nanoparticles

Abstract: ABSTRACT:We investigated changes in the Pt-Pt bond distance, particle size, crystallinity, and coordination of Pt nanoparticles as a function of particle size (1-3 nm) and adsorbate (H 2 , CO) using synchrotron radiation pair distribution function (PDF) and X-ray absorption spectroscopy (XAS) measurements. The ~1 nm Pt nanoparticles showed a Pt-Pt bond distance contraction of ~1.4%. The adsorption of H 2 and CO at room temperature relaxed the Pt-Pt bond distance contraction to a value close to that of bulk fcc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 51 publications
8
64
1
Order By: Relevance
“…Moreover,w ea lso observed spontaneous activity regeneration after deactivation and incubation period of individual Pt nanocatalysts.A st he example shows in Figure 3c for the regeneration (*), this nanoparticle initially shows high catalytic activity with aT OF of 13.4 min À1 for reaction R2, after af ew periods of electrocatalytic HOR reaction (R1) through CV scans;t he TOF for R2 decreases hugely to 1.6 min À1 ;while with longer a R1 process,the TOF for R2 on this nanoparticle increases inversely to 12 min À1 step by step, indicating an effective activity regeneration of the Pt nanoparticle.Asfor the incubation period observed on individual Pt nanoparticles,a ss hown in Figure 3c (&), initially,t his particle shows very low activity for R2,asthe electrocatalytic HOR reaction (R1)p roceeds,t he activity for R2 increases gradually;after amaximum TOF of 14.5 min À1 ,its activity for R2 decreases inversely,w hich is an ormal deactivation process.S tatistically,a bout 2% of the observable Pt nanoparticles show such kind of activity regeneration, and 3% of the nanoparticles show incubation period. According to previous results, [15] the activity regeneration of nanocatalysts could be mainly attributed to the binding/unbinding of some chemical intermediates on nanoparticle surface.I nt his case, the poisonous intermediates with strong binding on Pt could be the byproducts from carbon oxidation or corrosion since the long-term R2 reaction only leads to anegligible effect on the performance of Pt/G for R1 ( Figure S12). [5b, 16] As for the incubation period observed here on individual particle,i t could be attributed to the gradual exposure or formation of fresh active sites on the particle surface.…”
Section: Angewandte Chemiesupporting
confidence: 54%
“…Moreover,w ea lso observed spontaneous activity regeneration after deactivation and incubation period of individual Pt nanocatalysts.A st he example shows in Figure 3c for the regeneration (*), this nanoparticle initially shows high catalytic activity with aT OF of 13.4 min À1 for reaction R2, after af ew periods of electrocatalytic HOR reaction (R1) through CV scans;t he TOF for R2 decreases hugely to 1.6 min À1 ;while with longer a R1 process,the TOF for R2 on this nanoparticle increases inversely to 12 min À1 step by step, indicating an effective activity regeneration of the Pt nanoparticle.Asfor the incubation period observed on individual Pt nanoparticles,a ss hown in Figure 3c (&), initially,t his particle shows very low activity for R2,asthe electrocatalytic HOR reaction (R1)p roceeds,t he activity for R2 increases gradually;after amaximum TOF of 14.5 min À1 ,its activity for R2 decreases inversely,w hich is an ormal deactivation process.S tatistically,a bout 2% of the observable Pt nanoparticles show such kind of activity regeneration, and 3% of the nanoparticles show incubation period. According to previous results, [15] the activity regeneration of nanocatalysts could be mainly attributed to the binding/unbinding of some chemical intermediates on nanoparticle surface.I nt his case, the poisonous intermediates with strong binding on Pt could be the byproducts from carbon oxidation or corrosion since the long-term R2 reaction only leads to anegligible effect on the performance of Pt/G for R1 ( Figure S12). [5b, 16] As for the incubation period observed here on individual particle,i t could be attributed to the gradual exposure or formation of fresh active sites on the particle surface.…”
Section: Angewandte Chemiesupporting
confidence: 54%
“…A slight decrease of N Pt‐Pt and an increase of N Pt‐O were observed under WGSR conditions, compared to the analyses under H 2 flow. Despite the susceptibility to structural changes under an WGSR atmosphere and at high temperature, the results for 03PtAl_Cl and 2PtAl_Cl suggested that the variation of the structural parameters after activation under H 2 followed the same trend as under the WGSR atmosphere. Nonetheless, the behaviors of the reduced samples could be used to interpret the catalytic activity, as discussed below, since the structural parameters were not significantly different between the reduced and reaction conditions …”
Section: Resultsmentioning
confidence: 87%
“…[7] TheC O-protected Pt 13 cluster,which was derived from the as-synthesized Pt 13 in DPAG4-PyTPM,e xhibited as ingle peak attributed to [Pt 13 (CO) 15 ] 2À . [7] Similar to am ethod for the Pt 13 cluster synthesis,c arbon monoxide gas was introduced into the reaction vessel containing the Pt 19 cluster solution just after reduction of the [PtCl 4 ]/[DPAG4-PyTPM] = 19 assembly.Aspectrum of the resulting solution (Figure 2c)s hows the most intense peak at 2147.15 accompanied by many isotopes with 0.5 Da intervals,w hich is characteristic of divalent platinum cluster anions.T he distribution pattern of the isotopes around the main peak is equivalent to the calculated isotropic distribution of [Pt 19 -(CO) 21 ] 2À .B esides the main peak, similar divalent peaks accompanying similar isotopes and fragmentations were observed, each of which corresponds to [Pt n (CO) n+2 ] 2À (n = [16][17][18][19][20][21][22]. Based on the simplified assumption that the cluster yields correlate to the intensity in the mass spectrum, the visible distribution of the cluster atomicity is in good agreement with the distribution expected from the simulation (Figure 1b,d).…”
Section: Methodsmentioning
confidence: 81%
“…[1] One of the important concepts in recent cluster science is the superatom, which behaves as if it were ad ifferent element. [2] Although superatoms generally have spherical symmetry,arecent study by Castleman and colleagues indicated the prospect for the prominent reactivity of less symmetric clusters,a s exemplified by astudy on the unique reactivity of Al 17 À in the gas phase. [3] How are the activities of less symmetric clusters as catalysts?T oa nswer this question, precise synthesis at almost aone-atom resolution is necessary.However,there has been no synthetic method available to allow one-atom precision, except for the especially stable magic number clusters.…”
mentioning
confidence: 99%